If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x(3x + 9) = 0 Reorder the terms: -5x(9 + 3x) = 0 (9 * -5x + 3x * -5x) = 0 (-45x + -15x2) = 0 Solving -45x + -15x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '-15x'. -15x(3 + x) = 0 Ignore the factor -15.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {0, -3}
| 12.4g-34.3=9.5-3.1g | | =4x+10y | | 2x=28x^4 | | 5x=8x-19 | | -5e-3=7 | | 28x^4/2x | | -12-5u=3 | | -6z-4=-22 | | 5-3(f-4)=13 | | 2(-4-3y)+6y=5 | | -15-2p=-65 | | 2x+-2=4x-4 | | X^2+8x+116=0 | | -3=-3-57b | | 2.2=-6+40.6 | | 4z-(z-8)=0 | | 4x^2+5+3x-2+x^2+8x= | | 8(8x+2)=208 | | 1/2*4/3*3.14*9 | | -2-2m=-20 | | 4m-12=6m+6 | | f(x)=(9X)cos(x) | | 5z+12=4z+5 | | (x^2-2)/2=7 | | 7(-3+6K)= | | 6+(-n)-7=-2 | | 3c-5c=9+4c | | 4x+5=1x+2 | | x/8-(-2)=-3 | | 61.2=6(m+3.6) | | 4w-6=3(w+1) | | 12x+2x=10x+20 |